Risk factors, person, place and time characteristics associated with Hepatitis E Virus outbreak in Napak District, Uganda - Amanya, Geofrey; Kizito, Samuel; Nabukenya, Immaculate; Kalyango, Joan; Atuheire, Collins; Nansumba, Hellen; Akena Abwoye, Stephen; Opio, Denis Nixon; Kibuuka, Edrisa; Karamagi, Charles (BMC infectious diseases, 2017)
Hepatitis E is self-limiting, but can cause death in most at risk groups like pregnant women and those with preexisting acute liver disease. In developing countries it presents as epidemic, in 2014 Hepatitis E Virus (HEV) outbreak was reported in Napak district Uganda. The role of factors in this setting that might have propagated this HEV epidemic, including host, agent, and environmental characteristics, were still not clear. This study was therefore conducted to investigate the risk factors, person, place and time characteristics, associated with the hepatitis E virus (HEV) epidemic in Napak district. Methods: Review of line lists data for epidemiological description and matched case control study on neighborhood and age in the ratio of 1:2 were used to assess risk factors for HEV outbreak in Napak. Cluster and random sampling were used to obtain a sample size of 332, (111 cases, 221 controls). Possible interaction and confounding was assessed using conditional logistic regression. Results: Over 1359 cases and 30 deaths were reported during 2013/2014 HEV outbreak. The mean age of patients was 29 ± years, 57.9% of cases were females. Overall case Fatality Ratio was 2.2% in general population but 65.2% in pregnant women. More than 94% of the cases were reported in the sub counties of Napak, 5.7% of cases were reported in the outside neighboring districts. The epidemic peaked in January 2014 and gradually subsided by December 2014. Risk factors found to be associated with HEV included drinking untreated water (OR 6.69, 95% CI 3.15–14.16), eating roadside food (OR 6.11, 95% CI 2.85–13.09), reported not cleaning utensils (OR 3.24, 95% CI 1.55–1.76), and being a hunter (OR 1.14, 95% CI 1.03–12.66). Conclusion: The results of this study suggest that the virus is transmitted by the feco-oral route through contaminated water. They also suggest that active surveillance and appropriate measures targeting community and routine individual health actions are important to prevent transmission and decrease the deaths.
Keywords: Hepatitis E; Epidemic; Uganda